An Analysis on Students’ Self Efficacy in Writing Skill Mastering English Study Program at Univeristy of Pahlawan Tuanku Tambusai - Tri Melani; Citra Ayu; Lusi Marleni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study focuses on self-efficacy in English writing skills. The purpose of this study was to determine the students' self-efficacy in English writing skills. This study uses a qualitative research design with a descriptive approach. To obtain data, the researcher used a questionnaire. This research was conducted by giving questionnaires to the participants. The findings reveal that it can be said that this study aims to determine students' self-efficacy in writing skills. Semester 2 and 4 students Tuanku Tambusai Bangkinang still experience a lot of low writing skills.